The Cost Structure of the Clean Development Mechanism - Rahman, Shaikh M. (World Bank, Washington, DC, 2014)
This paper examines the cost of producing emission reduction credits under the Clean Development Mechanism. Using project-specific data, cost functions are estimated using alternative functional forms. The results show that, in general, the distribution of projects in the pipeline does not correspond exclusively to the cost of generating anticipated credits. Rather, investment choices appear to be influenced by location and project type considerations in a way that is consistent with variable transaction costs and investor preferences among hosts and classes of projects. This implies that comparative advantage based on the marginal cost of abatement is only one of several factors driving Clean Development Mechanism investments. This is significant since much of the conceptual and applied numerical literature concerning greenhouse gas mitigation policies relies on presumptions about relative abatement costs. The authors also find that Clean Development Mechanism projects generally exhibit constant or increasing returns to scale. In contrast, they find variations among classes of projects concerning economies of time.